On the geometry of Riemannian manifolds with a Lie structure at infinity - Bernd Ammann; Robert Lauter; Victor Nistor (International Journal of Mathematics and Mathematical Sciences)
We study a generalization of the geodesic spray and give conditions for noncomapct manifolds with a Lie structure at infinity to have positive injectivity radius. We also prove that the geometric operators are generated by the given Lie algebra of vector fields. This is the first one in a series of papers devoted to the study of the analysis of geometric differential operators on manifolds with Lie structure at infinity.